ANALISIS PENERAPAN SISTEM BAGI HASIL PADA PEMBIAYAAN MUDHARABAH DI PT BPRS AL-FALAH BANYUASIN TAHUN 2021 - Beni Beni; Meriyati Meriyati; Choiriyah Choiriyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Profit sharing is the distribution of business results that have been carried out by the parties who entered into the agreement, namely the customer and the sharia bank. In this case, there are two parties who enter into a business agreement, the results of the efforts carried out by both parties or one of the parties will be divided according to the portion of each party who entered into the contract agreement. The purpose of this research is to find out the application of the financing profit sharing system at PT. BPRS Al-Falah Banyuasin in 2021 and to find out what are the inhibiting factors for the implementation of the financing system at PT. BPRS Al-Falah Banyuasin. This type of research is a descriptive qualitative research. The data collection techniques used include observation, interviews and documentation. Based on the results of the study, it was concluded that the implementation of the Mudharabah financing profit sharing system carried out by PT. BPRS Al-Falah Banyuasin is using the Profit sharing method because it is in accordance with the recommendation of the MUI DSN Fatwa that the Profit Sharing method is more appropriate for Mudharabah financing. As for the obstacles in the implementation of Mudharabah financing at PT. BPRS Al-Falah Banyuasin is an obstacle when completing files or administrative requirements Constraints when the business is running.